Are Medicare wellness visits improving outcomes?. Issue 8 (23rd August 2021) - Watkins, Susan; Astroth, Kim Schafer; Kim, MyoungJin; Dyck, Mary J.
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: As the largest and unhealthiest population in American history enrolls as Medicare beneficiaries, it is vital for primary care providers to understand how to maximize Medicare wellness provisions. The Baby Boomer population has been documented to have the highest chronic disease prevalence related to preventable lifestyle behaviors. Perpetual unhealthy lifestyle behaviors associated with chronic disease prevalence are detrimental to life quality and the American Medicare resource structure. Since 2011, the Affordable Care Act provisions have included free wellness visits designed to prevent disease for Medicare beneficiaries, who continue to grossly underuse these services. Objectives: This systematic review was conducted to evaluate the quality, level, and strength of evidence regarding Medicare wellness service efficacy on related health outcomes. Data sources: The methodology adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for selection of 21 research-based articles included in the analysis. Results from the 21 eligible studies revealed low research quality and vigor; therefore, lacking causality and generalizability of medicare wellness visit (MWV) efficacy on health promotion outcomes. Conclusions: The evidence is focused on how MWVs are affecting preventive care utilization instead of patient health outcomes. In the interest of reducing chronic disease prevalence and the economic burden on our health care system, it is important to understand how these services affect health promotion outcomes. Implications for practice: The results of this systematic literature review substantiate the need for primary care providers to study MWV efficacy on health promotion outcomes for the Medicare population.